Understanding the parental contribution to antimicrobial resistance: a study of pediatric antibiotic practices in South Asian communities - Ghafoor, Saima; Idrees, Amna; Saad, Noor; Khalid, Mariyam; Rana, Mydah T.; Sajjad, Mohammad; Khalid, Muhammad Z. (International Journal of Contemporary Pediatrics, 2025)
Background: Antimicrobial resistance (AMR) is a growing public-health threat in South Asia. Because community AMR is shaped by parental knowledge, attitudes, and practices (KAP) regarding pediatric antibiotics, we assessed KAP among Pakistani parents and examined socioeconomic differences. Methods: A cross-sectional survey was administered from January 2024 to June 2025 in pediatric and pediatric-surgery outpatient clinics of five tertiary hospitals. Using multistage stratified random sampling, 425 parents of children aged 0–12 years completed a structured questionnaire spanning knowledge, attitudes, and practice domains. Results: Only 38.0% demonstrated appropriate knowledge of antibiotic use, while 61.9% incorrectly believed antibiotics treat viral infections. Self-medication with antibiotics was reported by 43.5%, frequently via over-the-counter purchase at pharmacies, and 45.9% stored leftover antibiotics. Lower household income (OR 1.79; 95% CI 1.26–2.55; p=0.003) and lower educational attainment (OR 2.14; 95% CI 1.52–3.00; p=0.001) independently predicted inappropriate antibiotic practices. Conclusions: Parental awareness and behaviors surrounding pediatric antibiotics in Pakistan are suboptimal, particularly among families with lower income and education. Addressing community-level AMR will require culturally tailored education, strengthened counseling by physicians and pharmacists, and enforcement of regulations limiting non-prescription antibiotic sales. Integrating stewardship messages into routine child-health visits and media campaigns, with monitoring through KAP surveys, may help curb misuse and preserve antibiotic effectiveness.